Application of proton-induced x-ray emission to a multielemental study of Bitter Pit in apples - Meyer, B. R.(Bernhard Rudolf) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1980.